The Impact of Loan Portfolio Returns on Stock Returns: The Moderating Role of Solvency in Jordanian Commercial Banks - Z. Al-Slehat (Финансы: теория и практика, 2023)
The current research aims is to test the impact of loan portfolio returns on stock returns in the Jordanian commercial banking sector in the presence of solvency as a conditional variable (moderator). Set in the research represents all Jordan’s local commercial banks listed on the Amman Stock Exchange for the period of 2013–2020. The SPSS program was used to achieve the study’s objective and test its hypotheses. The results showed significant impact of loan portfolio return on stock returns in the Jordanian banking sector. It means that loan portfolio return growth has an impact on shareholder stock returns as it depends on the bank’s financial performance. Solvency is a conditional variable to improve the impact of loan portfolio return on stock returns. Accordingly, the research presents a set of recommendations, Bank managers should focus on loan portfolio management and financial solvency in order to have greater profitability and follow the decisions which are passed by the Basel Committee.